(untitled) (TEST XY. Critical review of studies on the representation of architecture and use of the image in science and art, 2025)
The evolution of the contemporary city, dominated by the neoliberal consumerist logics, has led in the last century to a centripetal urbanism marked by commercial construction. These works, scattered across suburban areas and inherently indifferent to aesthetics, were conceived solely to serve market logic. Yet, after only a few decades, they lost their function and were abandoned, victims of the rise of digital commerce. These ‘commercial ruins’ represent a further simplification of the Vitruvian ratio, devoid of beauty and deprived even of utility. The inherent contradiction in consumerist architecture mirrors, in hyperbolic form, the evolutionary patterns of contemporary cities, making the study of representation crucial for its autopsy-like capacity to reveal transformations and activate regenerative processes through design. In addition to being analysed as products, they convey a language in constant evolution with respect to context; indeed, although genetically unified by the globalised stylistic features of marketing and standardised structures, these ‘selling machines’ are nonetheless dependent on the environment and culture in which they are grafted. It is therefore essential to define methodologies and processes to understand their detectable phenomena, identifying the structure and image to investigate their relationships and dynamisms, mechanisms of adaptation and survival of signs. Representative analysis delve into their semantic evolution to propose adaptive reuse aimed at sustainable regeneration. Commercial ruins are identified paradigmatically in Austria, where the building fabric, marked by a distinctive architectural language, is studied in its linguistic stratifications, revealing typological patterns that blur the traditional divide between the historic city and the suburbs. Even in their marginality, such areas retain the potential to incubate future development.